Influence of whey protein concentrate addition on textural properties of corn flour extrudates - Mladen Brnčić; Damir Ježek; Suzana Rimac Brnčić; Tomislav Bosiljkov; Branko Tripalo (Mljekarstvo)
Texture is an important propertiy of extruded snack products, and depended on extrusion process conditions, raw material properties and various ingredients properties as well. The main purpose of this research was, using twin-screw extrusion, to manufacture a direct expanded extrudate based on mixtures of corn flour and whey protein concentrate with acceptable textural properties. Mixtures were made of corn flour and three different concentrations of whey protein concentrate (7,5 %, 15 %, 22,5 %). Materials were processed in co-rotating twin-screw extruder APV Baker, MPF 50.15 under input conditions: water intake was 10,08 L/h, 12,18 L/h, 14,28 L/h, screw speed was 300 rpm; expansion temperature was 130 °C; feed rate was 70 kg/h. Textural properties: breaking strength index and expansion ratio were determined. Breaking strength index had largest value for the sample with 22,5 % of whey protein concentrate and water intake of 14,28 L/h. Sample with 7,5 % of whey protein concentrate and 10,08 L/h had largest expansion ratio. Calculated textural properties confirmed validity of samples. This results suggest that enrichment of extrudates with wpc addition up to 22,5 % to improve their nutritional value as well as their textural characteristics can be accomplished. Validation of direct expanded extrudates in dependence of its textural properties have shown validity and justification of this research.